Characterization of the Belowground Microbial Community in a Poplar-Phytoremediation Strategy of a Multi-Contaminated Soil - Barra Caracciolo, Anna; Grenni, Paola; Garbini, Gian Luigi; Rolando, Ludovica; Campanale, Claudia; Aimola, Giorgia; Fernandez-Lopez, Manuel; Fernandez-Gonzalez, Antonio José; Villadas, Pablo José; Ancona, Valeria (Frontiers in Microbiology, 2020)
Due to their widespread use in industrial applications in recent decades, Polychlorobiphenyls (PCBs) and heavy metals (HMs) are the most common soil contaminants worldwide, posing a risk for both ecosystems and human health. In this study, a poplar-assisted bioremediation strategy has been applied for more than four years to a historically contaminated area (PCBs and HMs) in Southern Italy using the Monviso poplar clone. This clone was effective in promoting a decrease in all contaminants and an increase in soil quality in terms of organic carbon and microbial abundance. Moreover, a significant shift in the structure and functioning of the belowground microbial community was also observed when analysing both DNA and cDNA sequencing. In fact, an increase in bacterial genera belonging to Proteobacteria able to degrade PCBs and resist HMs was observed. Moreover, the functional profiling of the microbial community predicted by PICRUSt2 made it possible to identify several genes associated with PCB transformation (e.g. bphAa, bphAb, bphB, bphC), response to HM oxidative stress (e.g. catalase, superoxide reductase, peroxidase) and HM uptake and expulsion (e.g. ABC transporters). This work demonstrated the effectiveness of the poplar clone Monviso in stimulating the natural belowground microbial community to remove contaminants and improve the overall soil quality. It is a practical example of a nature based solution involving synergic interactions between plants and the belowground microbial community.